Surgical Treatment of Elongated Styloid Process Causing Hypoglossal Nerve Compression, Leading to Tongue Atrophy and Limited Tongue Movement: A Case Report - Jeungchotipat, Parapat; Kanjanapaisit, Kongkrit; Baiadul, Sineerat (Srinagarind Medical Journal, 2025)
Background and Objective: The styloid bone is a structure that appears as a long, thin, needle-like rod protruding from the lower part of the temporal bone. It may extend beyond its normal length, which can compress surrounding structures and lead to hypoglossal nerve compression. This may cause speech abnormalities, difficulty swallowing, and atrophy of the tongue. Surgical intervention or not depends on the size of the lesion. This article reports the success of surgery on an abnormally longer styloid bone measuring than 4-5 cm, relieving compression on the hypoglossal nerve, leading to complete cessation of tongue twitching without any numbness and normal of tongue muscle function gradually restoration. Method: A 36-year-old male patient who presented with the complaint of accidentally biting the right side of his tongue while chewing food, followed by right-sided tongue twitching. After undergoing a CT scan, it was found that the right styloid bone measured 5.4 cm in length, which would be the cause of symptoms. The aim of this study was to assess the characteristics and symptoms related to the function of the tongue before and after surgery, focusing on the measurement of tongue atrophy in both resting and protruding positions, graded from 0 to 2, including tongue twitching and paresthesia. Results: After surgery to remove the excessively long styloid bone, the tongue twitching and paresthesia were completely resolved within the first hour post-operation. Tongue muscle function began to recover gradually starting on the 5th day, and complete recovery by the 1st month after surgery. Conclusion: This report presents a case report of a patient with abnormally long styloid bone, which led to compression of the hypoglossal nerve controlling the tongue muscles. Surgical removal of the excess styloid bone restored normal tongue function completely.